Consumers’ influence in sustainable decarbonisation of future power system - Šiljkut, Vladimir (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
Environmental protection and sustainable development cause a qualitative shift towards cleaner technologies in the field of electrical power. Countries with electricity generation from fossil fuels has questionable future energy independence and security of end-users supply. Therefore, it is necessary to explore all possible options for future development, not only as mutually alternative, but also taking into account their synergistic potential in compensating electricity deficit that will arise after shutdown of fossil fuel power plants. It is necessary to mutually harmonize development and application of different solutions. For example, the large share of renewable energy sources with highly variable generation, without the presence of significant energy storage capacities or other sources that could compensate these rapid fluctuations in power, causes problems in system balancing and disrupts its flexibility and stability. Among the supporting pillars of a secure and decarbonized power system, special attention will be paid to the possible role and contribution of consumers; increasing their energy efficiency, using the heat capacity of buildings, demand response and direct demand side management.
Keywords: capacity, decarbonisation, demand, fossil fuels, generation, reponse